Studies in tectonic culture : the poetics of construction in nineteenth and twentieth century architecture - Frampton, Kenneth (MIT Press, 1995)
This text aims to clarify the various turns that structural engineering and tectonic imagination have taken, showing how both constructional form and material character were integral to an evolving architectural expression.